Commercial Mastitis Vaccines - Effects on Mastitis Rates and Somatic Cell Counts in Saanen Goats - Bozkurt, Gokhan; Tasal, Ibrahım (Acta Scientiae Veterinariae, 2023)
Background: Staphylococcus spp. are the most frequently isolated microorganisms in mastitis cases of small ruminants. The virulence factors of Staphylococcus spp. are critical in the treatment. Therefore, preventive medicine and mastitis control programs, especially herd vaccinations are of great importance in the prevention of mastitis. However, it is not always easy to obtain these vaccines under field conditions. This study, it was aimed to compare the effects of different commercial Staphylococcus spp. vaccines licensed for bovines and species-specific mastitis vaccines on mastitis rates and somatic cell count on Saanen goats on field conditions. Materials, Methods & Results: The animal material consisted of 115 (230 udder halves) nulliparous Saanen goats. Goats were randomly grouped as bovine vaccine 1 (BV1, n = 58), bovine vaccine 2 (BV2, n = 58), small ruminant vaccine (SRV, n = 56), and control (n = 56). Vaccines were administered to goats in 2 doses according to the label regimen. First milk samples were collected between 0-5 days in milk (DIM) for microbiological analysis and 25-35 DIM for SCC. The other milk samples were collected at 25-35 (1st month) DIM, 60-65 (2nd month) DIM, 85-95 (3rd month) DIM, 115-125 (4th month) DIM, 145-155 (5th month) DIM for microbiological analysis and SCC. Non-aureus staphylococci (NAS) and S. aureus were the most frequently isolated microorganism. It was found that the total mastitis rate decreased in vaccine groups compared to the control group. A significant difference was found only in the BV2 and SRV groups. The significant difference in Staphylococcus aureus infection was found only in the SRV group. Mastitis vaccines used in this study decreased the NAS mastitis rate, but no significant difference was observed. It was found that the clinical mastitis incidence decreased in all vaccine groups compared to the control group, and a significant difference was found between the BV2 and SRV groups compared to the control group (P < 0.05). Somatic cell count was lower in the SRV and BV2 groups compared to the control group (P < 0.05). Discussion: In this study, compatible with the previous reports NAS and Staphylococcus aureus were the most frequently isolated microorganism. The diversity of virulence factors of Staphylococcus spp. also plays an important role in its high incidence. In some countries, mastitis vaccines used in cows are also administered to small ruminants for reducing infection rates. Similarly, in this study, it was found that the mastitis rate decreased in all vaccine groups compared to the control group. A significant difference was found only in the BV2 and SRV groups. It is thought that the reason for the statistical difference may be due to the biofilm antigen in the BV2 and SRV. In addition, J5 strain in the BV2 is estimated to be effective in reducing the prevalence of gram-negative mastitis. It was observed that the infection rates decreased in the vaccine groups, especially due to S. aureus and NAS. Spontaneous treatment rates were very close to each other between the groups. The reason for the high rate of spontaneous treatment in this study can be explained by the fact that the animals were young and in their 1st lactation. SCC was lower in all vaccine groups compared to the control group. This situation is associated with the decrease in infection rates related to the use of vaccines. It was observed that SCC was lower in the vaccine groups. In addition, SCC was found to be lower in this study compared to similar studies. However, it is evident that the use of species-specific vaccines in the SRV group significantly reduced the rates of total S. aureus mastitis, subclinical NAS mastitis, and new infections by NAS compared to other vaccines. Furthermore, the species-specific vaccine significantly increased the rate of spontaneous treatment for S. aureus mastitis. Keywords: field condition, mastitis, milk, Non-aureus staphylococci, small ruminant, vaccine.